Managing Education in The Era of Global Pandemic: Seeking the Best Strategy to Carry Out Natural Science Teaching In 4th Grade Elementary School - Munastiwi, Erni (International Journal of Elementary Education, 2021)
Exploration of teaching/learning model alternatives is important to carry out optimum education practice to the students. This research aimed to evaluate learning achievement of 4th grade elementary students in natural science, to analyze the impact of teaching/learning method and material source on students’ achievement, and to determine the best strategy in the management of educational practice for natural science subject during Covid-19 pandemic. The research was carried out in SDN Ungaran I Yogyakarta. Survey experimental was used as the research design, occupying the 2 x 2 factorial design. The factors were including teaching/learning method that included the online and blended learning and source of teaching/learning materials that included the textbook and internet. Data collection was carried out through online survey using google form. Data analysis was carried out through t-test and factorial Anova. Partially, only teaching/learning method had significant impact on students’ learning achievement, shown by t-test result of -2.610 (p=0.010). Teaching/learning method and source of teaching/learning simultaneously affected students’ achievement of natural science lesson. F-test obtained the value of 80.335 (p=0.001). The combination of blended learning and internet sourced teaching/learning materials resulted in significantly higher score achievement. Therefore, it is recommended as the model of delivering natural science lesson for 4th grade elementary school students.